Generic prescribing, brand and generic substitution, availability and cost effectiveness of the available medicines - Khanal, D.P.; Adhikari, P.; Chapagain, S.; Rayamajhi, S.; Nakarmi, S.; Adhikari, B. (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Background: Pharmaceuticals play a key role in the prevention and treatment of disease. The worldwide availability of effective, safe and affordable pharmaceuticals is a key challenge for the global public health system. Large economic interests are at stake within the field of pharmaceuticals. Pharmaceutical sales are existed as trade in many part of developing world including Nepal. At the same time, consumers (patients) are at mercy and unable to judge the quality, safety and, in many cases, the efficacy of the medicine, as well as whether the price is reasonable or not. They depend on others for assured quality medicines. Objective of this study was to find out the prescription written in generic name, availability of generic medicine in hospital pharmacy and outside pharmacy and cost effectiveness of brand –generic substitution in Manmohan Memorial Hospital Premises, Shyombu Kathmandu.Methods: All relevant information of brand-generic medicines and generic prescribing were recorded from the patient chart stored at medical record department except orthopedic department. In Orthopedic department, OPD prescriptions were recorded. Hospital pharmacy and outside pharmacy have been audited for the availability of generic medicines. Face to face interview with pharmacists in hospital and Drug Retailers were taken regarding the medicine available in generic name and medicine substitution. The recorded data were analyzed.Results: Only 298 out of 5120 medicines were found in generic name mostly from medical department, 215 medicines out of 812 medicines. There was no any single generic prescription in orthopedic department. In the hospital pharmacy and outside pharmacy have very few generic medicines. So no question of brand substitution by generic here. Mostly some large volume parental were available in generic names.Conclusion: Only 5.82 % of medicines were prescribed in generic name. Concerns over the therapeutic equivalence of branded products and generics are common amongst physicians, pharmacists and industries of course.JMMIHS.2018;4(1):33-42